KEPUTUSAN PEMBELIAN PASIEN RAWAT INAP DI RUMAH SAKIT WIYUNG SEJAHTERA: KAJIAN TERHADAP BAURAN PEMASARAN : Purchasing Decisions for Inpatients at Wiyung Sejahtera Hospital: A Study of the Marketing Mix - Mega, Adhella Eria; Drastyana, Serlly Frida; Rizky, M.Risya; Sutha, Diah (LPPM - STIKES Pemkab Jombang, 2023)
Hospital success is the main goal or vision of the hospital to provide services or products that are beneficial to the entire community at large (consumers). Hospitals will be able to win market competition if the hospital's products or services are more popular and trusted than other hospitals. The performance report on the marketing department of Wiyung Sejahtera Hospital shows that the marketing target achievement in 2022 does not meet the KPI (key performance indicators) target, but the hospital's engagement rate/BOR (Bed occupation rate) reached 82.35%, this is deemed necessary to carry out a suitability analysis. This study aims to analyze the relationship between marketing mix and purchasing decisions for inpatients at Wiyung Sejahtera Hospital. This type of research uses analytical research with a quantitative approach, cross sectional method. Data analysis used the Kendall's Tau test, sampling used simple random sampling. The findings of this study show that there is a relationship between the marketing mix of Price, Promotion, Place, Process, and Physical Evidence. physical) with purchasing decisions. Provides a better understanding of the importance of marketing mix management in the healthcare industry, especially in hospitals. By understanding how these factors relate to patient purchasing decisions, Wiyung Sejahtera Hospital can take more effective actions to improve marketing performance and fulfill its vision of providing quality services to the community.